KONSEP BERPIKIR DALAM ALQURAN - Ahmad Badwi (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2016)
The term thinking as the root of the word think the meaningful intellect, memory, and then the word is laced with the prefix